Drug reaction with herbal supplement: a possible case of drug induced lupus erythematosus - Muthupalaniappen,, Leelavathi A.; Jamani, Nurjasmine Aida; Muhammad , M.; Jamil, Adawiyah; Aziz , Noor Azah (Academy of Family Physicians of Malaysia, 2010)
A 24-year-old lady presented with four days history of fever, non-pruritic rash, ankle pain and swelling. She had consumed herbal supplement five days before the onset of symptoms. Examinations revealed erythematous maculo-papular lesions of varying sizes on sun exposed areas. Patient was suspected to have Drug Induced Lupus Erythematosus (DILE) and subsequently symptoms subsided rapidly on withholding the herbal medication.